PENGARUH SALES GROWTH TERHADAP TAX AVOIDANCE DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Lidwina Christine Mau (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The purpose of this study is to determine the effect of profitability on tax avoidance with corporate social responsibility as a moderating variable. In this study, the sample used was manufacturing companies listed on the Indonesia Stock Exchange (IDX) and for the 2015-2019 period, based on the purposive sampling method, 44 companies were obtained. The data in this study were processed using SPSS with multiple linear regression and absolute difference value test. The hypothesis testing method uses a significance level of 5%. The results showed that sales growth had a positive effect on tax avoidance. Corporate social responsibility cannot moderate the negative effect of sales growth on tax avoidance